Энергетический баланс тектоносферы Земли - Гордиенко, В.В. (Геофизический журнал, 2015)
Розглянуто концентрації K, U и Th у породах земної кори і верхньої мантії платформ, геосинкліналей та океанів. Виявлено збіг сумарного сучасного тепловиділення в корі і верхній мантії трьох типів регіонів за істотної розбіжності у розподілі джерел тепла за глибиною. Розраховано величини радіогенної теплогенерації порід верхньої мантії цих регіонів: близько 0,04, 0,06 і 0,08 мкВт/м³ відповідно. Для платформ установлено відповідність теплогенерації геологічній історії, тепловому потоку та глибинним температурам. Доведено виконання закону збереження енергії у геологічних процесах. Concentration of K, U and Th has been investigated in the rocks of the Earth's crust and upper mantle of platforms, geosynclines and oceans. The coincidence has been found between total modern heat emanation in the crust and upper mantle of three types of regions with significant differences in the distribution of sources in depth. The values of upper mantle rocks radiogenic heat generation in these regions are about 0,04, 0,06 and 0,08 мW/m³ respectively. Correspondence of heat generation to geological history, heat flow and deep temperatures has been set for platforms. Implementation of energy conservation law in geological processes has been proven.